THE EFFECT OF M-PAJAK AND E-FORM USE ON MSMEs' TAX COMPLIANCE IN PEMATANG SERAI VILLAGE, LANGKAT REGION - Eka Susilawaty, Tengku; Azzahra, An Suci (Proceeding International Seminar of Islamic Studies, 2023)
The tax administration reform carried out by the Directorate General of Taxes is an effort to optimize its services so that taxpayers are not reluctant to carry out their obligations, so as to increase taxpayer compliance. M-Pajak and E-Form are types of tax administration reforms launched by the Directorate General of Taxes with the aim of making it easier for taxpayers to obtain tax services that are more personal and fast and for income tax reporting that can be used by MSMEs in carrying out their tax obligations. This study aims to test whether the use of M-Pajak and the use of E-Form affect the compliance of UMKM taxpayers in Pematang Serai Village, Langkat Region. This research approach is quantitative using the survey method, where the author distributes questionnaires for data collection as well as the data analysis techniques used in this study, including descriptive statistics and multiple linear regression methods with the Classical Assumption Test, t-test, F-test, and D-test. The results of this study indicate that the use of M-Pajak and the use of E-Form both partially and simultaneously affect taxpayer compliance.